Una escritura de rescate. El discurso vacío en la obra de Levrero - Reinaldo Laddaga (Cuadernos LIRICO)
Mario Levrero’s late novels are composed of fragments taken from his (spiritual, mental, bodily) exercise notebooks. In these works, writing is presented as a means to recover from those fragments, the passing presence of a subject that can only be captured in flight. My essay analyzes the way this process is described in his book El discurso vacío (The Empty Speech) and proposes an interpretative approach to his late enigmatic